1991
DOI: 10.1002/j.1537-2197.1991.tb15751.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and Interfertility Relationships of Arachis Section Arachis

Abstract: Twenty‐nine recently introduced diploid (2n = 2x = 20) accessions of section Arachis plus an A. correntina (Burk) Krap. et Greg. nom. nud. control were hybridized to the diploid A‐genome species A. duranensis Krap. et Greg. nom. nud. (ace. 7988), the diploid B‐genome species A. batizocoi Krap. et Greg. (acc. 9484), and with two subspecies of the A‐B genome (2n = 4x = 40) A. hypogaea cultivars NC 4 and Argentine. Most attempted crosses were successful and the resulting plants were vigorous. However, A. batizoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
3

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 12 publications
1
24
1
3
Order By: Relevance
“…"A" chromosomes are exclusive of section Arachis. Furthermore, the hybrids between A. duranensis (section Arachis) x A. chiquitana obtained by STALKER et al (1991) have shown 54% of pollen staining and a bivalent average pairing of 9,97 and of 18,52 chiasmas per PMC. This is indicating a high affinity between both species.…”
Section: Resultsmentioning
confidence: 99%
“…"A" chromosomes are exclusive of section Arachis. Furthermore, the hybrids between A. duranensis (section Arachis) x A. chiquitana obtained by STALKER et al (1991) have shown 54% of pollen staining and a bivalent average pairing of 9,97 and of 18,52 chiasmas per PMC. This is indicating a high affinity between both species.…”
Section: Resultsmentioning
confidence: 99%
“…4. Further, a principal component analysis using karyotypic data grouped taxa into three distinct clusters which were equidistant from each other [13]. [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The perennial species of the section Arachis have 20 chromosomes, including Husted's A pair and show more similarity and better crossability to each other than those that do not have the A pair, generally being classified as the A genome species (Stalker, 1989; Stalker et al, 1991). The same applies to the annual A. duranensis and A. stenosperma Krapov.…”
mentioning
confidence: 99%